2020
DOI: 10.1055/s-0040-1713835
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus and Its Impact on Dental Fraternity

Abstract: The coronavirus disease-2019 (COVID-19) is a pandemic the world is currently facing head on. It is a viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). No current vaccine is available nor a curative treatment option is available at present, thus making it even more important to prevent the disease. Since dentists are in very close contact with their patients and there is aerosol production in various dental treatments, they are at a heightened risk of contracting the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…22 An Indian study reported that the patients were charged additionally for PPE. 23 Although, in our study, most of the tenants agreed that the cost of PPE should be included in patients' treatment fees, yet charging patients an infection control fee may result in unethical custom. Induction of PPE cost in the aforementioned patient fee may have a significant impact on accessing care, especially for patients of a lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 70%
“…22 An Indian study reported that the patients were charged additionally for PPE. 23 Although, in our study, most of the tenants agreed that the cost of PPE should be included in patients' treatment fees, yet charging patients an infection control fee may result in unethical custom. Induction of PPE cost in the aforementioned patient fee may have a significant impact on accessing care, especially for patients of a lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 70%
“…There have been 43 publications on COVID-19 in JHAS-NU since the journal began in 2016, but the subject of all except for 6 of these articles is direct patient care. Three 1 2 3 have some diagnostic care component and the subject of the other three is the laboratory diagnosis of COVID-19. 4 5 6 Since JHAS-NU began in 2016, there have been 2 publications on biofilms, 7 8 3 publications on the microbiome, 9 10 11 2 publications on nanotechnology, 12 13 and 1 publication on probiotics.…”
mentioning
confidence: 99%